2008
DOI: 10.1590/s0102-311x2008000500021
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos climáticos em áreas de transmissão de hantavirose no Estado de São Paulo, Brasil

Abstract: The objective of this study was to investigate the spatial distribution of reported hantavirus cases in São Paulo State, Brazil (n = 80), from 1993 to 2005 and identify local climatic patterns during this period. Kernel point estimation of density was used to show the highest concentrations in Ribeirão Preto, São Carlos, Franca, Tupi Paulista, and Greater São Paulo. Increase in the number of cases during this period suggests disease dissemination even when considering increased diagnostic capacity and higher s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
1
6
0
6
Order By: Relevance
“…The DF climate is characterized by two seasons: rainy and dry (19) . The peak incidence of HPS was reported during the dry and cold season, which was also observed in a presumably descriptive study in Uberlândia, Minas Gerais that included only 23 cases during an 8-year period (32) and in the State of São Paulo, as reported using a sophisticated scientifi c method (33) . In contrast, a seasonal pattern was not found in another study of Brazilian geographical regions (BGRs) (26) .…”
Section: Methodssupporting
confidence: 61%
“…The DF climate is characterized by two seasons: rainy and dry (19) . The peak incidence of HPS was reported during the dry and cold season, which was also observed in a presumably descriptive study in Uberlândia, Minas Gerais that included only 23 cases during an 8-year period (32) and in the State of São Paulo, as reported using a sophisticated scientifi c method (33) . In contrast, a seasonal pattern was not found in another study of Brazilian geographical regions (BGRs) (26) .…”
Section: Methodssupporting
confidence: 61%
“…This may have been related to the fact that the dry season from May to September 2007 was exceptionally hot and dry. Donalisio et al 16 observed that the rainfall in inland municipalities in the state of São Paulo in 2007 was low. This weather pattern may have brought hungry wild rodent populations closer to humans in rural areas, looking for harvested grains and other kinds of food.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, changes in urban and rural environments were associated with emergence of new infectious diseases (eg, Brazilian haemorrhagic fever, hantaviruses). [20][21][22] Diseases that were previously well controlled were reintroduced to Brazil (dengue 17 ) or underwent epidemiological changes that compromised their eff ective control (visceral and cutaneous leishmaniases, 13 hepatitis C 23 ). 24 Reductions in mortality from some diseases were not always accompanied by reduction in incidence; tuberculosis and HIV/AIDS are still a public health problem in many regions of the country, despite substantial decreases in mortality rates since the mid-1990s.…”
Section: Key Messagesmentioning
confidence: 99%